Optimasi Taguchi Menggunakan Metode Vikor dalam Pemilihan Ban Mobil - Fauzhia Rahmasari; Fogot Endro Wibowo; Thoriq Aziz Taufiqurrahman (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2022)
The main functions of tire are to withstand the vehicle’s load, continue the steering function and control the vehicle’s direction, transmit the driving force and vehicle’s braking on the road surface and reduce shock vibrations from the road surface. Therefore, optimal tire selection is something that needs to be considered for driving perfection. Taguchi methods is one of experimental design methods that is often used because of considerations of effectiveness and efficiency. However, Taguchi methods only can be used to solve a single response optimization problem. When dealing with multi-response problems, the responses are analyzed separately. This study aims to optimize Taguchi design using VIKOR method in production of car tires. The experimental design and responses used in this study were derived from car tire production data which analyzed using VIKOR methods and selected based on the optimum value to obtain the optimal combination of factors levels. The results of Taguchi's analysis are the first and third responses indicating the 16th experiment and second response indicating the 14th experiment which is the optimal combination. It can be concluded that Taguchi methods is inconsistent to producing optimal combination of levels of factors when dealing with multi-response problems, so additional methods are needed as Taguchi optimization methods in solving multi-response problems, including using VIKOR methods which results in the 2nd experiment being optimal combination.